Increasing public speaking capabilities for youth organization Persatuan Pemuda Mangindara - Wardah Wardah; Syukri Syukri; Ahmad Syarif; Muhammad Yahya (Universitas Muhammadiyah Magelang, 2022)
Persatuan Pemuda Mangindara is a youth organization that has the obligation of helping to create the welfare of the villagers. The problem found that youth organization members are generally still clumsy and do not have sufficient knowledge and skills in terms of public speaking. For this reason, public speaking training is needed that helps increase self-confidence and provides knowledge and basic speaking techniques. This public speaking training is carried out in several stages, starting from the preparation stage (observation and interview), the implementation stage (pre-presentation, initial evaluation, orientation, post-presentation, and feedback), and the evaluation stage. This training provides knowledge and improves basic public speaking skills for youth organization members to become good presenters, able to deliver speeches correctly and be more confident in interacting, communicating, and socializing with the community.